Equine acupuncture methods and applications: A review - Pellegrini D.Z.* (2020)
© 2018 EVJ LtdThis review discusses the applications of acupuncture (AP) and its eastern medical philosophy in equine health, and the main techniques used to stimulate acupoints in equine practice. These methods include dry needling, electroacupuncture (EA), moxibustion, laser therapy, haemopuncture, aquapuncture, pharmacopuncture, acupressure and gold implants.